The cluster 1 type VI secretion system is a major virulence determinant in Burkholderia pseudomallei. - Burtnick, M; Brett, P; Harding, S; Ngugi, SA; Ribot, W; Chantratita, N; Scorpio, A; Milne, T; Dean, R; Fritz, D; Peacock, S; Prior, J; et al. (2011)
The Burkholderia pseudomallei K96243 genome encodes six type VI secretion systems (T6SSs), but little is known about the role of these systems in the biology of B. pseudomallei. In this study, we purified recombinant Hcp proteins from each T6SS and tested them as vaccine candidates in the BALB/c mouse model of melioidosis. Recombinant Hcp2 protected 80% of mice against a lethal challenge with K96243, while recombinant Hcp1, Hcp3, and Hcp6 protected 50% of mice against challenge. Hcp6 was the only Hcp constitutively produced by B. pseudomallei in vitro; however, it was not exported to the extracellular milieu. Hcp1, on the other hand, was produced and exported in vitro when the VirAG two-component regulatory system was overexpressed in trans. We also constructed six hcp deletion mutants (Δhcp1 through Δhcp6) and tested them for virulence in the Syrian hamster model of infection. The 50% lethal doses (LD(50)s) for the Δhcp2 through Δhcp6 mutants were indistinguishable from K96243 (<10 bacteria), but the LD(50) for the Δhcp1 mutant was >10(3) bacteria. The hcp1 deletion mutant also exhibited a growth defect in RAW 264.7 macrophages and was unable to form multinucleated giant cells in this cell line. Unlike K96243, the Δhcp1 mutant was only weakly cytotoxic to RAW 264.7 macrophages 18 h after infection. The results suggest that the cluster 1 T6SS is essential for virulence and plays an important role in the intracellular lifestyle of B. pseudomallei.